Modeling bayesian updating with many non-updaters: the case of own subjective homicide victimization risk - Costa, Yuri Lacerda (2015)
Our main purpose in this study is to investigate the role of heterogeneity into the update of subjective homicide victimization risk after an informational shock. In this sense, the data used here also attests the crime overestimation found in the literature. The novelty is that our respondents faced an informational shock consisting in the official homicide rate, but the vast majority of them keeps the same initial perception. In proposing a Bayesian Update model allowing that no update takes place, two models were developed: a modified Tobit and a two-tiered Hurdle model. In accordance with previous papers, our results showed that we could proceed with a Bayesian Update approach. Also, the higher initial responses are set, more likely individuals are in proceeding a change in perceptions. Furthermore, fundamentally, we could rationalize a non-updating decision following a perceived informational quality/credibility argument. We found that older participants and females are more reluctant not only to change initial responses, but also to choose the level of the new response, in case of an update. In addition, respondents’ level of education was insignificant in our exercise. In fact, interviewers’ level of education had a key role in both the changing and updating magnitude decisions. Finally, our results also raised strong evidence on homophily aspects. The occurance of a matching in gender between interviewers and interviewees had a major impact on the decision to change and in the magnitude of the update in this study.